Identity polyphony and dual discourse in the prose of Irvine Welsh - Gonchar-Khanjyan, Natalie (Bulletin of Yerevan University B: Philology, 2024)
Contemporary fiction increasingly relies on the latest psychological discoveries in its choice of themes and plot construction, which in turn are often anticipated by literary examples.A striking illustration of such literary insight is Stevenson's famous story, which laid the foundation for a new literary approach to the theme of the double and doppelganger, going beyond the purely literary example. The images of Jekyll and Hyde in literature built on the antinomy of two or more antagonist characters are considered archetypal. Although Stevenson himself was directly influenced by Dostoevsky, in whose work the theme of the double is a leitmotif, it was Stevenson who, with his Strange Case..., gave impetus to the further development of the phenomenon of the doppelganger in contemporary literature, both globally and nationally – within Scottish literature.Having already become iconic, the hypostases of Stevenson's doubles are reflected in the works of Scotsmen Iain Banks («The Bridge», «Complicity»), Alasdair Gray («Lanark: A Life in Four Books»), and in a number of novels by Irvine Welsh. Welsh chooses the theme of the double, traditional in Scottish prose since Stevenson’s time, as a central concept in his texts, passing his characters through the initiation of dissociative disorder and sublimating his own lived and integrated experiences into his writing.In the broad field of literary criticism, references to Welsh's texts are rare compared to other examples of transgressive prose. Probably this is due to the difficulty of understanding his author’s concept, the multi-layered composition, as well as the plots that are repulsive in their demonstrative aggressiveness, their deliberately depressive content, the overt manifestation of taboo topics combined with an abundance of obscene language, as well as the deliberate secrecy of the writer himself, who rarely gives interviews and avoids other marketing moves to promote his books. Thus, an attempt to conduct a scientific analysis of the texts of a writer whose work is of both literary and psychological interest makes this topic relevant, and the approach to studying Welsh’s texts through the lens of split personality contributes to the novelty of the research.The purpose of the article is to present the dual discourse in the writer’s novels covering the period from 1995 to 2016.
Keywords: double; abuse; initiation; sublimation; transgression; Welsh